A DISCOURSE ANALYSIS OF FIGURATIVE LANGUAGE USED IN THE LECTURE OF USTAD ABDUL SOMAD LC.MA.: A DISCOURSE ANALYSIS OF FIGURATIVE LANGUAGE - Shally Amna (Universitas Muhammadiyah Muara Bungo, 2019)
The research is aimed to analyze a discourse of figurative languages used in the lecture of Ustad Abdul Somad, LC.MA. (UAS) which is held in Pasaman District, West Sumatera province.The research is qualitatively descriptive approached. In conducting the research, the data are collected by using documentation technique. The data are categorized by referring to Perrine’s category namely personification, metaphor, hyperbole and paradox. The Data are transcript from Indonesian language into English language. To analyze the data, the research uses discourse analysis and descriptive method. The findings of the research are 98 expressions of figurative languages found in the lecture of UAS for 70 minutes namely 34.6 % the expressions of paradox, 25.5% the expressions of hyperbole, 20.4% the expression of metaphor and 19.3 % the expression of personification. These figures are analyzed by using the context of the utterances.